Highly active carbon supported palladium-rhodium PdXRh/C catalysts for methanol electrooxidation in alkaline media and their performance in anion exchange direct methanol fuel cells (AEM-DMFCs). (10th September 2015) - Jurzinsky, T.; Bär, R.; Cremers, C.; Tübke, J.; Elsner, P.
Highlights: Synthesis and physical evaluation of carbon supported, Rh containing Pd electrocatalysts. Electroactivity towards methanol oxidation strongly enhanced in alkaline media. Bimetallic catalyst show low CO oxidation and OH adsorption potentials. CO2 current efficiency higher for bimetallic catalysts than for Pt/C or Pd/C. Power density of 105 mW cm −2 for platinum-free alkaline direct methanol fuel cell. Abstract: In this study carbon supported PdX Rh electrocatalysts synthesized by wet chemical reduction process were tested for the potential use in anion-exchange membrane direct methanol fuel cells (AEM-DMFC) and compared to Pd/C and commercially available Pt/C. A metal loading of 20wt% on carbon was confirmed by thermogravimetric analysis (TGA) and catalyst compositions of PdRh3 /C, PdRh/C and Pd3 Rh/C were found via inductively coupled plasma optical emission spectroscopy (ICP-OES). Transmission electron microscopy (TEM) and x-ray diffraction (XRD) studies showed that the average particle and crystallite sizes of the PdX Rh/C catalysts are in the range of 3.1 to 4.3 nm. It was also found that these catalysts are not alloyed. Cyclic voltammetry (CV) data reveals a 85–140 mV lower CH3 OH oxidation onset potential and higher mass current densities for PdX Rh/C catalysts compared with Pd/C. Steady-state measurements via chronoamperometry (CA) showed a good stability against poisoning during methanol oxidation and higher mass activities for PdRh/C and Pd3 Rh/C compared to Pt/C. By using differential electrochemical mass spectrometry (DEMS) it was successfully shown that adding Rh to Pd results in an enhanced CO2 current efficiency (CCE) compared to Pd/C or Pt/C. AEM-DMFCs free from platinum were fabricated and single cell tests at 60 °C showed a significant increase of power density at 0.5 V cell potential from 4.8 mW cm −2 for Pd/C to 16.5 mW cm −2 for PdRh/C with the anode and cathode fed with 1 M methanol + 2 M KOH and synthetic air, respectively. Peak power density of 104.9 mW cm −2 was reached for PdRh/C anode catalyst at 80 °C using higher KOH and methanol concentrations in anodic fuel and oxygen as cathodic oxidizer.